The Relationship Between Data, Technology, and Humanism Literacy and Integrity in Lecturer Research Performance - Suharsiwi Suharsiwi; Fauzi Fauzi; Laila Yumna; Rohimi Zamzam (Universitas Muhammadiyah Malang, 2023)
In an era driven by technological progress, lecturers, as the main agents in academic research, are faced with the demand to understand and integrate data, technology, and human values into their research. The purpose of writing this article is to describe the research performance of lecturers based on the factors of data literacy, technological literacy, and humanism literacy, as well as the integrity of lecturers in higher education. This research method involves surveys and data analysis by a number of lecturers who are active in research in various scientific disciplines. This research method also uses a quantitative approach and a cross-sectional study design. Data was collected through a Google Form questionnaire distributed via WhatsApp. The research data was analyzed using multiple regression (OLS). This article contributes to an understanding of the importance of integrating data literacy, technology, and human values into lecturers' research approaches. The practical implication of this research is the need to develop training programs and institutional support to increase literacy and integrity in the context of academic research. The research results show that literacy and data integrity have a significant effect on lecturers’ research performance. Meanwhile, technological literacy and humanism literacy do not have a significant effect on lecturers' research performance. Lecturers’ research performance through the results of this research is influenced by variations in data literacy, technological literacy, humanism literacy, and integrity by 36.1%.